Antibacterial Activity Test of Ethanol Extract From Unripe Klutuk Banana Fruit (Musa Balbisiana Colla Bb) Towards Bacterial Of Staphylococcus Aureus And Escherichia Coli - M, Misrahanum; Depi, Ririn Edra; Helwati, Hira (Asian Journal of Pharmaceutical Research and Development, 2021)
Object : This study aims to look at antibacterial activity Ethanol extracts from the flesh and peel of unripe klutuk banana fruit (Musa balbisiana Colla BB) against Staphylococcus aureus and Escherichia coli. Methods : Study included phytochemical screening, simplicial and extract characterization, antibacterial testing using a well diffusion method ethanol extracts from the flesh and peel of unripe klutuk banana fruit (Musa balbisiana Colla BB) against Staphylococcus aureus and Escherichia coli. Results : The phytochemical test showed that both extracts contained alkaloid compounds, flavonoids, tannins, triterpenoids, and saponins. The fruit simplicial characterization of the flesh and peel contains 5% and 7.17% of water level; 14.55% and 11.61% of total ash level; 10.67% and 9.67% of water-soluble level; 9.67% and 9.67% of ethanol-soluble level. The ethanol extracts of the flesh and peel of unripe klutuk banana contains water level of 28.26% and 15.5%;total ash level of 10.16% and 14.09%; water-soluble level of 33.33% and 71.67%, and ethanol-soluble level of 69.16% and 78.33%. The highest activity of the peel ethanol extract towards S. aureus was obtained at 10% concentration with an inhibiting zone diameter of 9.3 mm and the highest activity of the flesh ethanol extract towards E. coli was obtained at 20% concentration with an inhibiting zone diameter of 8.63 mm. Conclusion : Antibacterial activity against S. aureus by the ethanol extract from the peel was higher than ethanol extract from the flesh of the fruit. While antibacterial activity towards bacterial E. coli by the flesh of fruit showed better activity.